2019
DOI: 10.1111/liv.14015
|View full text |Cite
|
Sign up to set email alerts
|

Increased interleukin‐23 receptor (IL‐23R) expression is associated with disease severity in acute‐on‐chronic liver failure

Abstract: Abbreviations: ACLF, acute-on-chronic liver failure; CCR6, chemokine receptor 6; CHB, chronic hepatitis B; CTP, Child-Turcotte-Pugh; GM-CSF, granulocyte-macrophage colony-stimulating factor; IL-17R, interleukin-17 receptor; IL-23R, interleukin-23 receptor; IL-, interleukin; INR, international normalized ratio; MELD, Model for End-Stage Liver Disease; ROR-γt, retinoic acid receptor-related orphan nuclear receptor gamma t. AbstractBackground: Th17 cells mediated immune response is important in chronic hepatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Currently, the pathogenesis of CHB is not well elucidated. Accumulating evidence suggests that Th17 cells are critically involved in the pathogenesis of liver diseases, including CHB, 22 HBV‐related cirrhosis 5 and ACLF 23 . Our previous studies also confirmed that the proportion of Th17 cells is significantly increased in CHB, HBV‐ACLF 7 and HBV‐LF 8 .…”
Section: Discussionsupporting
confidence: 82%
“…Currently, the pathogenesis of CHB is not well elucidated. Accumulating evidence suggests that Th17 cells are critically involved in the pathogenesis of liver diseases, including CHB, 22 HBV‐related cirrhosis 5 and ACLF 23 . Our previous studies also confirmed that the proportion of Th17 cells is significantly increased in CHB, HBV‐ACLF 7 and HBV‐LF 8 .…”
Section: Discussionsupporting
confidence: 82%
“…The present knowledge and understanding of the innate immune response of ACLF patients is limited. There are a number of specific issues left somewhat ambiguous, like whether a dysregulated innate immune response is the cause or outcome of Induces systemic inflammatory pathways, is associated with disease severity, short term mortality (34,123) IL-8 Neutrophil infiltration, liver inflammation, short term mortality (51,53,123) IL-10 Associated with poor prognosis and mortality (136) IL-17 Associated with clinical disease severity markers including INR and MELD, mortality, recruits proinflammatory cells, increases the expression of profibrogenic factor TGF-β, and inflammatory cytokines IL-6 and IL-23 (121,136,137) IL-22 Hepatoprotective, supports liver regeneration, attenuates bacterial infection (127,130) IL-23 Associated with clinical disease severity markers MELD, INR, prothrombin time, total bilirubin, and mortality (101,121) G-CSF and G-MSCF Reduces IFN-γ production, mobilizes CD34+ cells, improves clinical disease severity indices and survival in ACLF patients, reduces short term mortality, activates progenitors to promote differentiation and activation of monocytes and neutrophils (36,46,99,(138)(139)(140)(141) TGF-β Liver injury, disease severity, and poor survival in ACLF (122) VCAM-1, ICAM-1 Inflammation, short term mortality (36) ACLF. Few studies outlined abnormal innate immunity of ACLF patients which is associated with systemic inflammation, disease progression, and pathogenesis; however extensive research is required to find out the mechanisms responsible for disease severity and high mortality in these severely ill patients.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic circulatory dysfunction and exacerbation of systemic inflammation leads to organ failure(s). (53,99,(117)(118)(119)(120)(121)(122)(123). The majority of these cytokines are related to the innate immune response such as leukocyte migration, particularly monocytes and macrophages, chemotaxis pathways, endothelial dysfunction, and subsequently induces systemic inflammation.…”
Section: Cytokine Responses During Aclfmentioning
confidence: 99%
“…In this study, there was no difference in levels of IL-12 and IL-23 in subjects with viral hepatitis compare to non-viral hepatitis. This could be caused by the presence of IL-12 and IL-23 in other types of hepatitis such as autoimmune hepatitis ( 35 ) and alcoholic hepatitis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%